Situation awareness in critical infrastructures. (1st January 2014) - Abate, Vincenza; Adacher, Ludovica; Pascucci, Federica
Critical infrastructure(CI) protectionand situationawarenessarerelevanttopicsin critical system domain. These issuesgofarbeyond the academicworldinvolvingvery often the national security framework. In this contribution, a review of the most attractive approaches proposed for addressing the situation awareness problems is presented. Most of the proposed approaches are based on multi-sensor data fusion, since the awareness is achieved by building a scenario using data providedby sensors spread into the systems. Humans are supposed to interact with the system, but only a few models are able to include their intervention. The review analysis is performed by considering models, architectures, and techniques adopted in each system and by highlighting their effectiveness and drawbacks. Finally an example in the ﬁeld of air trafﬁc management is presented.